The diagnostic value of quantitative bone SPECT/CT in solitary undetermined bone lesions - Du, Fen; Wumener, Xieraili; Zhang, Yarong; Liu, Ming; Li, Taichuang; Huang, Size; Zhang, Maoqun; Wu, Rongliang; Liang, Ying (Frontiers in Oncology, 2023)
Objective To investigate the diagnostic value of the maximum standard uptake value (SUVmax) of quantitative single-photon emission computed tomography/computed tomography (SPECT/CT) in solitary undetermined bone lesions. Methods In Part I, retrospective study, 167 untreated patients with extra-skeletal malignant tumors by pathology were consecutively enrolled for staging with Tc-99m methyl-diphosphonate (99mTc-MDP) whole-body bone scan (WBS) and quantitative SPECT/CT, and a total of 396 bone lesions with abnormal radioactivity concentration in 167 patients were included from April 2019 to September 2020. The differences in SUVmax among the benign bone lesions, malignant bone lesions, and normal vertebrae were analyzed. The receiver operating characteristic (ROC) curve and cutoff value of SUVmax were obtained. Part II, prospective study, 49 solitary undetermined bone lesions in SPECT/CT in 49 untreated patients with extra-skeletal malignant tumors were enrolled from October 2020 to August 2022. The diagnostic efficacy of SUVmax in solitary undetermined bone lesions was assessed. The final diagnosis was based on follow-up imaging (CT, MRI, or 2-deoxy-2-[18F]fluoro-D-glucose-positron emission tomography/computed tomography) for at least 12 months. Results In Part I, a total of 156 malignant and 240 benign bone lesions was determined; the SUVmax of malignant lesions (26.49 ± 12.63) was significantly higher than those of benign lesions (13.92 ± 7.16) and normal vertebrae (6.97 ± 1.52) (P = 0.00). The diagnostic efficiency of the SUVmax of quantitative SPECT/CT revealed a sensitivity of 75.00% and a specificity of 81.70% at a cutoff value of 18.07. In Part II, 17 malignant and 32 benign lesions were determined. Using SUVmax ≥18.07 as a diagnostic criterion of malignancy, it has a sensitivity of 82.35%, a specificity of 93.75%, and an accuracy of 89.80%. Conclusion The SUVmax of quantitative SPECT/CT is valuable in evaluating solitary undetermined bone lesions. Using a cutoff SUVmax value of 18.07, quantitative SPECT/CT demonstrated high sensitivity, specificity, and accuracy in differentiating malignant from benign bone lesions.